Answer :


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = √3 b = -2√2 c = -2√3


= √3.-2√3 = -2.3 = -6


And either of their sum or difference = b


= -2√2


Thus the two terms are -3√2 and √2


Difference = -3√2 + √2 = -2√2


Product = -3√2 × √2 = -3.2 = -6




(On using3√2 = √3 √3 √2 = √3.√6)



(2√3 = √2 √2 √3 = √2.√6)




Roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics